Pembuatan Prototype Insert Carbide Dari Material Metal Matrix Composite dengan Teknologi Serbuk Metalurgi dan Pengujiannya - Fata Taoziri; Jata Budiman; Wiwik Purwadi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2025)
The effective use of cutting tools such as carbide inserts is crucial in the manufacturing industry, especially in machining processes involving hard materials. Carbide inserts are a type of cutting tool used to cut materials in machining processes. This research aims to discuss the experiment of producing carbide insert test specimens using the powder metallurgy technology process and made from Metal Matrix Composite material. The research method employed is the design of experiments with the Taguchi method. The controlled parameters are Fe (%), namely Binder (%), and mixing time (minutes). The response measured is the hardness value (HV). The contribution of the process parameters influencing the response value is found to be Fe = 11.90%, Binder = 54.70%, and mixing time = 30.99%. The experimental results yield a hardness value of 1534.778 HV. In conclusion, the most influential parameter in carbide insert production through powder metallurgy technology is the Binder (%) with a contribution of 54.70%.